1994
DOI: 10.1111/j.1365-3016.1994.tb00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with high risk of perinatal and neonatal mortality: an interim report on a prospective community‐based study in rural Sudan

Abstract: In a community-based prospective study, 6275 deliveries resulting in 6084 livebirths, 150 stillbirths (SB) and 167 neonatal deaths (NND) were monitored over a period of 3 years. The risk of an unfavourable outcome (SB or NND) in multiple pregnancies was more than ninefold that of singletons. Teenage mothers and those over 34 years of age ran nearly twice the risk of having an unfavourable outcome of pregnancy compared with mothers aged 20-29 years. First pregnancy and grand-multiparity (greater than eight prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
1
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 13 publications
4
24
1
2
Order By: Relevance
“…Generally the only health providers in their remote communities, their duties include antenatal care, referral of high-risk pregnancies, home deliveries, postnatal care, registration of births and limited drug dispensation. In Sudan, the proportion of women delivered at home by VMWs remained unchanged at 80% between 2006 and 2010,1 2 3 while a 2010 national survey showed that first-month neonatal mortality remained static at 1990s levels of 41 per 1000 live births 4…”
Section: Introductionmentioning
confidence: 99%
“…Generally the only health providers in their remote communities, their duties include antenatal care, referral of high-risk pregnancies, home deliveries, postnatal care, registration of births and limited drug dispensation. In Sudan, the proportion of women delivered at home by VMWs remained unchanged at 80% between 2006 and 2010,1 2 3 while a 2010 national survey showed that first-month neonatal mortality remained static at 1990s levels of 41 per 1000 live births 4…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have assessed how sociodemographic patterns are related to neonatal mortality in Africa. [11][12][13][14] Previous reviews of the causes of neonatal deaths have demonstrated that up to 70 per cent of neonatal mortality could be prevented using evidence-based interventions. To adopt a focused, evidence-based approach to reduce neonatal mortality in Swaziland, a clear understanding of the associated factors is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Weerasekera pointed out that prenatal care and socioeconomic factors may be more important to pregnancy outcome than maternal age 9 . Ibrahim and co-workers conducted a prospective study to determine the factors linked to perinatal and neonatal mortality in a rural community in Sudan 10 . Poor pregnancy outcome was more likely for teenage mothers and a first pregnancy.…”
mentioning
confidence: 99%